Mitochondrial Function in Oxidative and Glycolytic Bovine Skeletal Muscle Postmortem - Lindsey C Bell; Patricia Maloso Ramos; Stephanie Wohlgemuth; Tracy Scheffler (Meat and Muscle Biology, 2021)
Meat quality is traditionally associated with anaerobic metabolism due to cessation of the oxygen supply post-mortem. However, mitochondrial (mt) function early postmortem may affect the development of meat quality characteristics, such as adenosine triphosphate levels and pH decline. Therefore, the objective of this study was to evaluate mt function ex vivo during the first 24 h postmortem in muscles with differences in mt content. Samples from longissimus lumborum (LL) and diaphragm (Dia) were taken from steers (n = 6) at 1, 3, and 24 h postmortem and frozen to determine citrate synthase (CS) activity and mt protein expression (immunodetection) or were fresh-preserved for high-resolution respirometry. Integrative oxygen consumption rate (picomoles per second per milligram of tissue) was measured and normalized to CS activity as a proxy for mt content (intrinsic mt function, picomoles per second per unit CS). CS activity (P < 0.001) and mt protein expression (P < 0.001) were greater in Dia, which was reflected in mt respiration. Muscle type affected (P < 0.001) integrative leak respiration and was greater in mt from Dia; oxidative phosphorylation (OXPHOS) was also greater in Dia and influenced by time postmortem (muscle × time: P = 0.01). Intrinsic leak and OXPHOS were affected by muscle and time (muscle × time: P = 0.05 and P = 0.01, respectively), with the most pronounced differences at 24 h postmortem. Stimulation of OXPHOS by cytochrome c as an indicator of outer mt membrane integrity was influenced by muscle and time postmortem (muscle × time: P = 0.03); it was greater in mt from LL. Despite intrinsic differences in respiratory function at 24 h, mt from both muscles were intact and coupled at 1 h postmortem. Reduced content and respiratory function in mt from LL are associated with early fragmentation, which could impact protease activation and subsequently meat quality.